Subarachnoid Fentanyl as Adjuvant to Hyperbaric Bupivacaine Prevents Perioperative Shivering Among Parturient Undergoing LUCS Under Spinal Anaesthesia- A Prospective Study - Das , Tapas Kumar; Ullah, Mohib; Banik, Shyamal Chandra; Das, Mitu (Journal of Dhaka National Medical College & Hospital, 2023)
Background: Post Spinal Anaesthesia Shivering (PSAS) is one of the most common problems during spinal anaesthesia. Shivering is being treated with some drugs. Objective: To evaluate the efficacy of intrathecal fentanyl in prevention of shivering in patients undergoing LUCS under spinal anaesthesia. Methodology: This prospective study was done among 60 patients of ASA I and II divided into two groups of 30 each. Group A was given a combination of 10 mg (2 mL) of hyperbaric 0.5% bupivacaine with 25 μg (0.5mL) fentanyl intrathecally and group B was given only 10 mg (2 mL) of hyperbaric 0.5% bupivacaine. Shivering was observed in both groups for 3 hours. Results: Among the 30 patient of group A only 3 patients (10%) developed shivering whereas among the 30 patient of group B 18 patients (60%) developed shivering. So the incidence of shivering in Group A was significantly lower than Group B. Conclusion: Intrathecal fentanyl is effective in decreasing the frequency of perioperative shivering in parturient undergoing LUCS under spinal anaesthesia. J. Dhaka National Med. Coll. Hos. 2023; 29 (01): 30-33